1971
DOI: 10.1111/j.1365-2141.1971.tb02706.x
|View full text |Cite
|
Sign up to set email alerts
|

The Chromosomes of Bone‐Marrow Cells of Haematologically Normal Men and Women

Abstract: Summary. An analysis was made of the chromosomes of 1301 marrow cells from 59 haematologically normal men and women. No case of total aneuploidy was found. The overall incidence of aneuploidy in the population of 1301 marrow cells was 10.3%; hypodiploid 10%, hyperdiploid 0.3%. In the group of 15 individuals where 50 cells could be analysed the proportion of aneuploid cells differed very significantly from person to person. In contrast to the situation in myeloproliferative disorders, hyperdiploidy in normal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In cultured T lymphocytes of females, aneuploidy of the X chromosome is observed more frequently than aneuploidy of the Y chromosome in males. In contrast, there appears to be little or no X chromosome aneuploidy in bone marrow cells of normal females or of females with a haematological malignancy (Secker Walker, 1971) although Y chromosome loss is very frequent in bone marrow of both normal males and those with a haematological malignancy. However, it is not possible to determine whether the age and tissue differences in sex chromosome aneuploidy between males and females is the result of differences in the frequency with which such aneuploidy occurs or results from selective factors operating differently in males and females.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In cultured T lymphocytes of females, aneuploidy of the X chromosome is observed more frequently than aneuploidy of the Y chromosome in males. In contrast, there appears to be little or no X chromosome aneuploidy in bone marrow cells of normal females or of females with a haematological malignancy (Secker Walker, 1971) although Y chromosome loss is very frequent in bone marrow of both normal males and those with a haematological malignancy. However, it is not possible to determine whether the age and tissue differences in sex chromosome aneuploidy between males and females is the result of differences in the frequency with which such aneuploidy occurs or results from selective factors operating differently in males and females.…”
Section: Discussionmentioning
confidence: 95%
“…Chromosome studies of bone marrow from men who did not have haematological disease were also found to have 45,X cells, in a similar proportion to that in patients with haematological malignancy (O'Riordan et al , 1970; United Kingdom Cancer Cytogenetics Group (UKCCG), 1992). There are very few published data on sex chromosome aneuploidy in the marrow cells of females with or without a haematological malignancy, but it appears that X chromosome aneuploidy is not a feature of the marrow cells of ageing women (Secker Walker 1971). …”
mentioning
confidence: 99%
“…It appears that in this patient euploidy was restored following therapy. It has been shown by two groups of workers (O'Riordan et al 1970, Secker Walker 1971) that elderly, haematologically normal males may lack a Y chromosome in a minor population of bone marrow cells. Major populations of 45, X, Ycells may be found in constitutionally normal males with chronic myeloproliferative disorders (Speed & Lawler 1964.…”
Section: Discussionmentioning
confidence: 99%
“…Mosaicism can result from mitotic errors during early cleavage of the zygote but it may occur in somatic tissues at any stage of life. Acquired mosaicism is seen in the bone marrow of elderly males who show a propensity to loss of Y chromosomes in varying proportions of the cells (O'Riordan et al, 1970;Secker Walker, 1971). …”
Section: Mosaicismmentioning
confidence: 99%